11. RESULTS OF CARE OF PATIENTS AFTER LIVER REsection DUE TO KLATSKIN TUMOR AT THE DEPARTMENT OF HEPAGODA, BILIARY, AND PANCREATIC SURGERY, K HOSPITAL (Vietnam Journal of Community Medicine, 2025)
This retrospective descriptive study was conducted at the Department of Hepatobiliary and Pancreatic Surgery in K Hospital from January 2017 to October 2024 to evaluate post-operative care outcomes for patients undergoing liver resection due to Klatskin tumors. The study included 22 patients diagnosed and surgically treated for hilar cholangiocarcinoma (types IIIa, IIIb, and IV) with comprehensive medical records. Results showed a higher prevalence in males (68.18%) compared to females (31.82%), with a mean age of 63.1 ± 9.2 years. The primary reasons for hospital admission were jaundice (59.1%) and right upper quadrant pain (36.4%). Most patients underwent preoperative biliary drainage (81.8%) and major liver resections (59.1%), with an average incision length of 23.5 ± 7.9 cm and a mean operative duration of 241.5 ± 61.1 minutes. Post-operative care activities were thoroughly implemented, with 100% of patients monitored for vital signs and wound care at least twice daily during the first three days. The average duration of antibiotic use was 11.70 ± 4.31 days, and the average time for abdominal drain removal was 9.07 ± 2.89 days. Common early post-operative complications included ascites (22.7%), liver failure (13.6%), and bile leakage (9.1%). Pre-discharge evaluations indicated that 63% of patients had good care outcomes. The study highlights the critical role of nursing in close monitoring and comprehensive care for patients after liver resection due to Klatskin tumors to ensure early detection and timely management of complications.
Keywords: Klatskin tumor; hepatectomy; postoperative care; care outcomes; nursing